Analisis Penggunaan Kecerdasan Buatan terhadap Kemampuan Berpikir Kritis Mahasiswa Informatika: Pendekatan MMSLR - Louise Gabriella; Usman Arfan; Imanuel Aji Karisteo (Jurnal Publikasi Teknik Informatika, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed learning processes in higher education, particularly in Informatics education, where critical thinking skills are essential for solving computational problems. On the one hand, AI offers various advantages in accessing information, supporting problem-solving activities, and improving learning effectiveness. On the other hand, inappropriate use of AI may lead to cognitive dependency that can affect students' critical thinking abilities. This study aims to analyze the relationship between AI usage and the critical thinking skills of Informatics students through a Mixed Method Systematic Literature Review (MMSLR) approach. The study integrates quantitative mapping and qualitative synthesis of 25 selected articles retrieved from several academic databases based on predetermined inclusion criteria. The findings indicate that AI can function as cognitive scaffolding that supports analysis, evaluation, reflection, and problem-solving processes. Furthermore, AI literacy and self-regulated learning were identified as key factors influencing the effectiveness of AI utilization in learning activities. However, passive use of AI without information verification may reduce students' engagement in independent thinking processes. This study highlights the importance of integrating AI literacy and self-regulated learning into AI-based educational strategies to strengthen critical thinking skills in higher education.